PEDAGOGY THROUGH ICT: FINDINGS ON CREATIVITY OF TECHNOLOGICAL STUDENTS AND PERSEPECTIVE TEACHERS OF HARYANA (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
Education may be the largest part of triumphant foundation to emerge from the industrial age. Twentieth century nations have thrived for the reason that they identified and employed effective strategies for education and employment of the general population. The world is changing. Technology makes us smarter. In todays pedagogy, technology is not only a tool, but also a resource for accessing information. Day after day, new ways have been used to amalgamate technology into learning process. This paper deals with the imperative effect on creativity with pedagogy through information and communication technology tools. Survey method of research has been used in this work, for which the computations have been performed through chi-square test in statistical package for social sciences (SPSS).The results shows the imperative effect of use of information and communication technology tools to enhance creativity of the students.